Sejarah Perkembangan Psikologi Pendidikan - Nur Fadilah; Satria Panji Nugraha; Prihaten Maskhuliah (STIKes Ibnu Sina Ajibarang, 2025)
Educational psychology has evolved from the thoughts of Ancient Greek philosophers. The development of educational psychology was greatly influenced by the contributions of figures such as William James and John Dewey. Educational psychology has been influenced by various schools of psychology, including behaviorism, cognitivism, and humanism. Educational psychology has made significant contributions in various areas of education, such as curriculum development, learning design, and education evaluation. Research in educational psychology has helped improve learning effectiveness and meet the needs of diverse students. The development of educational psychology cannot be separated from the social and cultural context. Factors such as social change, technological advances, and global issues have shaped the direction of educational psychology development.